Opportunistic use of 3G uplink licensed bands - Marques, P.
Radio frequency spectrum is a highly expensive commodity. However, UMTS UL bands capacity has been mainly underutilized due typical Internet traffic asymmetry. In this paper we consider a secondary wireless system that operates over the UMTS UL bands in an opportunistic way. The opportunistic radios (OR) sense the path loss between its location and the UMTS base station. With this sensing information the ORs adapts its power to avoid harmful interference with the UMTS system. Sensing is performed exploiting cyclostationary features of the UMTS signal and no cooperation between the two networks is assumed. Spectrum opportunities are computed and coexistence between the two wireless networks is analyzed.